Cardiac effects of antimalarial treatment with halofantrine. - Nosten, F; ter Kuile, F; Luxemburger, C; Woodrow, C; Kyle, D; Chongsuphajaisiddhi, T; White, N (1993)
In a prospective electrocardiographic study of Karen patients with acute uncomplicated falciparum malaria, mefloquine (25 mg/kg) had no cardiac effects (n = 53), but halofantrine (72 mg/kg) induced consistent dose-related lengthening of the PR and QT intervals in all 61 patients treated. The likelihood of significant QTc prolongation (by more than 25% or a QTc of 0.55 s1/2 or more) was greater after halofantrine as retreatment following mefloquine failure than as primary treatment (7/10 vs 18/51; relative risk 2.0 [95% Cl 1.1-3.4], p = 0.04). More than 60% of the effect occurred with three doses of halofantrine (24 mg/kg). The arrhythmogenic potential of halofantrine should now be investigated.